Criminal law aspects of combating phishing and carding (Phishing and carding as forms of fraud in the digital environment: legal qualification) - Dusmatov Durbek Rustamjon ugli (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The article examines phishing and carding as forms of fraud committed in the digital environment from the perspective of criminal law. It analyzes the specifics of their legal qualification under the legislation of the Russian Federation and foreign countries, identifying gaps and inconsistencies in the application of criminal law norms. The article also proposes directions for improving legislation and its enforcement practices to enhance the effectiveness of combating these types of cybercrime.